2021
DOI: 10.1002/er.6567
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole‐aided surface decoration of graphene oxide nanosheets as fillers for poly(ether‐ b ‐amid) mixed matrix membranes to enhance CO 2 capture

Abstract: Summary Modified graphene oxide (GO) nanosheets as fillers within poly(ether‐b‐amid) (PEBA) copolymer as matrix were used for mixed matrix membranes (MMMs) fabrication to improve CO2 capture. The GO nanosheets were modified by polypyrrole (PPy) and zinc cations. The former that have conjugated N‐containing groups provided a high degree of affinity toward CO2, and the latter has facilitated the gas molecules transport through the gas channel passages. The different modified GO nanosheets were characterized by H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 61 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Conductive polymer membranes were reported for H 2 separation (e.g., H 2 /CO 2 , H 2 /N 2 ), air purification, and CO 2 capture (e.g., CO 2 /N 2 , CO 2 /CH 4 ) in the form of self-supported membranes, composite membranes, and polymer blend membranes. Examples of conductive polymers that have been extensively reported for gas separation include PANI [ 111 , 467 , 468 , 469 , 470 , 471 , 472 , 473 , 474 , 475 , 476 , 477 , 478 , 479 , 480 , 481 ], polypyrrole [ 482 , 483 , 484 , 485 , 486 , 487 , 488 , 489 ], and polythiophene [ 490 , 491 , 492 ]. A comprehensive review of conductive polymer-based membranes for gas separation application was reported recently [ 117 ].…”
Section: Applications Of Hollow Fiber Membranesmentioning
confidence: 99%
“…Conductive polymer membranes were reported for H 2 separation (e.g., H 2 /CO 2 , H 2 /N 2 ), air purification, and CO 2 capture (e.g., CO 2 /N 2 , CO 2 /CH 4 ) in the form of self-supported membranes, composite membranes, and polymer blend membranes. Examples of conductive polymers that have been extensively reported for gas separation include PANI [ 111 , 467 , 468 , 469 , 470 , 471 , 472 , 473 , 474 , 475 , 476 , 477 , 478 , 479 , 480 , 481 ], polypyrrole [ 482 , 483 , 484 , 485 , 486 , 487 , 488 , 489 ], and polythiophene [ 490 , 491 , 492 ]. A comprehensive review of conductive polymer-based membranes for gas separation application was reported recently [ 117 ].…”
Section: Applications Of Hollow Fiber Membranesmentioning
confidence: 99%
“…GO nanosheets were also modified using polypyrrole and zinc cations [ 54 ] or by covalently grafting silane followed by the polyetheramine canopy (M2070) forming solvent-free hybrid nanofluids (denoted as GO NF) [ 38 ]. GO flakes functionalized with iron oxide (Fe 3 O 4 –GO) were aligned in the polymer matrix under a magnetic field ( Figure 5 ), demonstrating a better gas separation performance when vertically aligned than MMMs with a random arrangement of Fe 3 O 4 –GO [ 55 ].…”
Section: Materials For the Analysed Mmmsmentioning
confidence: 99%
“…An increase in the permeability of CO 2 as a polar gas with the increasing of the pressure was observed in MMMs filled with GO-PPy due to the increase in gas sorption [ 54 ]. Instead, the permeability of the bulkier CH 4 molecules was decreased due to the membranes having a more compact structure.…”
Section: Gas Separation Performancementioning
confidence: 99%
“…Asghari used modified graphene oxide nanosheets as fillers and poly(ether‐b‐amid) copolymer as a matrix to prepare MMMs. It was found to show good results in terms of CO 2 permeability, CO 2 /methane, and CO 2 /nitrogen selectivity 32 . Yoshimoto investigated the adsorption and diffusion behaviors of CO 2 , CH 4 , and N 2 in interfacial systems composed of a polymer of intrinsic microporosity (PIM‐1) and amorphous silica.…”
Section: Introductionmentioning
confidence: 99%
“…It was found to show good results in terms of CO 2 permeability, CO 2 /methane, and CO 2 /nitrogen selectivity. 32 Yoshimoto investigated the adsorption and diffusion behaviors of CO 2 , CH 4 , and N 2 in interfacial systems composed of a polymer of intrinsic microporosity (PIM-1) and amorphous silica. It was found that due to the competition effect on the silica surface, the MMMs formed larger pores and promoted the diffusion of CH 4 and N 2 gases.…”
Section: Introductionmentioning
confidence: 99%